IMPLEMENTASI MODEL DISCOVERY LEARNING MELALUI MEDIA E-LEARNING BERBASIS WORDPRESS UNTUK MENINGKATKAN PEMAHAMAN PEMBELAJARAN MATERI OPTIK FISIS DAN GEOMETRI - Azis Nugraha, Tubagus Abdul (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
WordPress is a very popular open source application used as a blogging engine which is widely used by several people as an innovation that makes work easier. By implementing the Discovery Learning model through WordPress-based e-learning media to increase understanding of physics learning in optical physics and geometry material. The purpose of implementing this WordPress application is as an alternative to help students understand material about optical physics and geometry that can be accessed anytime, anywhere to re-study or review previously studied material. So that the results of the stages that have been carried out can be embedded in students' memories regarding physics learning material and provide convenience and comfort for users. By making the presentation of the material attractive, it makes students feel more enjoyable. Therefore, the application of the Discovery Learning model through WordPressbased e-learning media is to increase understanding of physics learning in optical physics and geometry material.